Bioassay of steroid hormone agonist and antagonist activities of anti-androgens on mammary gland, seminal vesicles and spleen of male mice - Skarda, J (Journal of veterinary medicine. A, Physiology, pathology, clinical medicine, 2003)
Young intact and adult castrated outbred C3H/Di male mice were used to characterize steroid hormone agonist and antagonist activities of anti-androgens by bioassay. Animals were injected subcutaneously with flutamide (Flut), chlormadinone acetate (CMA), cyproterone acetate (CA) or Casodex (Cas) alone or simultaneously with oestradiol (E), E plus progesterone (Prog) or norethindrone acetate (NA; a steroid exhibiting progestational and oestrogenic activities) and testosterone (T) for 15 days. Mammary gland growth was not affected with anti-androgen alone. However, all anti-androgens decreased seminal vesicle weights in intact males. In E (0.01 microg day(-1))-treated intact males, mammary growth was stimulated by CMA (progestational activity) and inhibited by CA. The inhibitory effect of CA on mammary growth (glucocorticoid activity) was overcome with high dose of E (0.1 microg day(-1)). When seminal vesicles weights were decreased with a moderate dose of E (0.01 microg day(-1)) anti-androgens injected simultaneously acted synergistically with E and decreased seminal vesicles weights more than E alone. However, in animals overloaded with E (0.1 microg day(-1)), anti-androgen CA was unable to decrease seminal vesicles weights. E (0.01 or 0.05 microg day(-1)) or E + Prog (500 or 1000 microg day(-1)) or NA (12.5 to 50 microg day(-1)) stimulated mammary growth was inhibited by T at doses 20-200 microg day(-1) and these effects were decreased or abolished by simultaneous application of Flut, CMA or Cas in both young intact and adult castrated males. In the same animals, the seminal vesicles weights were increased by T and decreased by anti-androgens. The effects of higher doses of T (300 microg day(-1)) were not inhibited by anti-androgens both in the mammary gland and seminal vesicles. Spleen weights were not consistently affected with Flut, CMA or Cas, but decreased with CA by dose dependent manner. These results demonstrated that anti-androgenic activities could be detected not only on seminal vesicle but also on the mammary gland. Our model system also detected a glucocorticoid activity of CA and progestational activity of CMA.
Keywords: Mammary Glands, Animal; Orchiectomy; Steroids; Seminal Vesicles; tosylové sloučeniny; Flutamide; semenné váčky; antagonisté androgenů; Biological Assay; Drug Therapy, Combination; flutamid; chlormadinon; mužské pohlaví; outbrední kmeny zvířat; mléčné žlázy zvířat; Mice; Cyproterone Acetate; norethisteron acetát; orchiektomie; slezina; Animals, Outbred Strains; steroidy; progesteron; myši inbrední C3H; kombinovaná farmakoterapie; zvířata; Mice, Inbred C3H; Estradiol; Norethindrone; cyproteronacetát; Progesterone; Tosyl Compounds; myši; anilidy; biotest; Androgen Antagonists; Norethindrone Acetate; Chlormadinone Acetate; nitrily; Spleen; norethindron; estradiol; Anilides; Male; Nitriles; Animals